Analisis Konseptual Teori Dan Proses Pelaksanaan Kebijakan Publik - Putri Ayu Anisya (Pusat Riset dan Inovasi Nasional, 2024)
Public policy is essentially and what is based on authority and power, because public policy is made by a group of people who have legitimate power in a government system. Very often a public policy that is implemented does not side with the people, and only benefits one party. Therefore, public policies provided by the government must have the value of siding with the people so that their implementation is intended to resolve every problem. The purpose of this writing is to discuss conceptual analysis of theories and the process of implementing public policy. The results of the discussion show that public policy is a very important factor in achieving maximum government administration.